Relationship Between Fragmented QRS Complex and Left Ventricular Fibrosis and Function in Patients With Danon Disease - Xie, Jiajun; Liu, Yang; Wei, Xiaoyu; Ye, Weitao; Ma, Zelan; Lu, Guanyu; Tan, Zekun; Li, Tingyu; Wang, Yining; Zhao, Lei; Lu, Minjie; Li, Xiaohu; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Fragmented QRS (f-QRS) on surface electrocardiogram (ECG) is a cardiac conduction abnormality that indicates myocardial scarring. The relationship between the f-QRS complex and cardiac status in patients with Danon disease (DD) remains unclear and will be explored in this study. Methods: Patients with genetically confirmed DD and cardiac magnetic resonance imaging (CMR) examinations were recruited from multiple centres. The number of leads, pattern, score and segmental distribution of the f-QRS complex were assessed by surface 12-lead ECG. Cardiac status, including left ventricular (LV) volume, function, and extent of late gadolinium enhancement (LGE), was demonstrated by CMR. The segmental distribution of LGE was also assessed. Correlations between the f-QRS and cardiac status were assessed. Results: Fifteen patients (14 men) with DD who underwent 12-lead ECG and CMR imaging were included. The f-QRS complex was documented in all patients (n = 15, 100%). Three patterns of f-QRS were found, with the notched R/S pattern (74%) being the most common, followed by fragmented QRS (16%) and various RSR' (11%). The fragmented QRS pattern showed an association with higher level of myocardial fibrosis (LGE>35%). The burden of f-QRS in each patient was assessed by the number of leads with f-QRS (median 7, range 2-12) and the f-QRS score (median 9, range 2-33). In the correlation analysis, the f-QRS score was positively correlated with LGE% (r = 0.726, P = 0.002) negatively correlated with LV ejection function (r = −0.617, P = 0.014) as evaluated by CMR. In the local distribution, f-QRS score and LGE% were both predominant in the LV free wall but did not correlate well among the anterior, lateral, and inferior segments. Conclusion: In this DD cohort, the quantitative f-QRS correlated well with myocardial fibrosis burden and LV dysfunction in general. This finding suggests that f-QRS can be used as a simple screening tool to assess cardiac status in DD patients.